Geospatial evaluation and bio-remediation of heavy metal-contaminated soils in arid zones - Mohamed, Elsayed Said; Jalhoum, Mohamed E. M.; Hendawy, Ehab; El-Adly, Ahmed M.; Nawar, Said; Rebouh, Nazih Y.; Saleh, Ahmed; Shokr, Mohamed. S. (Frontiers in Environmental Science, 2024)
Soil pollution directly impacts food quality and the lives of both humans and animals. The concentration of heavy metals in Egypt's drain-side soils is rising, which is detrimental to the quality of the soil and crops. The key to reducing the detrimental effects on the ecosystem is having accurate maps of the spatial distribution of heavy metals and the subsequent use of environmentally sustainable remediation approaches. The objective of this work is to assess soil contamination utilizing spatial mapping of heavy metals, determine contamination levels using Principal Component Analysis (PCA), and calculate both the contamination severity and the potential for bioremediation in the soils surrounding the main drain of Bahr El-Baqar. Furthermore, evaluating the capacity of microorganisms(bacteria, fungi, and "Actinomycetes) to degrade heavy elements in the soil. 146 soil sample locations were randomly selected near the Bahr El-Baqar drain to examine the degree of soil pollution Ordinary Kriging (OK), method was used to map and analyze the spatial distribution of soil contamination by seven heavy metals (Cr, Fe, Zn, Cd, Pb, As, and Ni). Modified contamination degree (mCd) and PCA were used to assess the research area's soil pollution levels. The process involved isolating, identifying, and classifying the microorganisms present in the soil of the study area. The study findings showed that variography suggested the Stable model effectively matched pH, SOM, and Cd values. Furthermore, the exponential model proved suitable for predicting Fe ,Pb and Ni, while the spherical model was appropriate for Ni, Cr, and Zn. The study revealed three levels of contamination, with an extremely high degree (EHDC) affecting approximately 97.49% of the area. The EHDC exhibited average concentrations of heavy metals: